Improvement of Rheological Properties of Modified Asphalt Treated with Residues of Recycled Rubber from Waste Tires and Oxidized by Air - Al-Ojar, Roua’a K.; Mahmood, Mahmood E.; Marzena, Salam J.; Jabrail, Fawzi H. (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2024)
Asphalt materials loaded with polymer additives have gained particular importance in recent years due to their close association with modification processes and the creation of a clean environment, mainly from plastic wastes in paving and other areas, and they have also caused significant improvement in asphalt properties. It was observed through the research that the rheological properties of the asphalt were improved significantly as added residues of recycled rubber (RRR) from waste tire percentages increased. The observations are apparent from the decrease in permeability of the asphalt and enhance its ductility and elongation. The study focused on modifying the rheological properties of asphalt materials using the residues of the recycled process of rubber (RRR) from waste tires (mainly carbon black, containing residues of rubber extracted from waste tires). The asphalt materials were oxidized in the open system under various conditions of temperature and oxidation time in the presence of a 0.25% (w/w) anhydrous aluminum chloride (AlCl3) catalyst. After determining the optimal conditions for the oxidation process, the added anhydrous AlCl3 catalyst was adjusted to determine its optimal ratio. The modified asphalt samples after oxidation at optimal conditions in the presence of anhydrous AlCl3 catalyst and the recycled rubber (RRR) residues were tested using appropriate measurements. The following measurements of ductility, permeability, softening point, Marshall stability and flow, aging resistance (thin film oven test (TFOT)) and the asphalt content percentages were done, and their results show that the modified asphalt exhibits completely different rheological properties from the original asphalt. The studied N19 and N20 models show availability in paving applications.